1997
DOI: 10.1073/pnas.94.23.12551
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell ontogeny: A human dendritic cell lineage of myeloid origin

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
328
2
6

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(346 citation statements)
references
References 49 publications
10
328
2
6
Order By: Relevance
“…For comparison, the same populations of myeloid precursor cells that can be found in normal human cord blood is also shown in Table 2. These results demonstrate the presence in these mice of the same mDC precursors that are normally isolated from human peripheral blood, cord blood, and fetal bone marrow [2, 4, 13,20,21].…”
Section: Characterization Of Human DC Progenitor Cells In the Bone Mamentioning
confidence: 69%
See 1 more Smart Citation
“…For comparison, the same populations of myeloid precursor cells that can be found in normal human cord blood is also shown in Table 2. These results demonstrate the presence in these mice of the same mDC precursors that are normally isolated from human peripheral blood, cord blood, and fetal bone marrow [2, 4, 13,20,21].…”
Section: Characterization Of Human DC Progenitor Cells In the Bone Mamentioning
confidence: 69%
“…Previously, Nobuyoshi et al [12] reported human DCs present in the bone marrow of transplanted NOD/SCID mice with a CD34 -CD4 + HLA-DR + phenotype. Unfortunately, these analysis did not explore the nature of the different DC precursor/progenitor populations, and the criteria used to identify human DCs did not include analysis of CD11c or CD123 expression or analysis of expression of blood dendritic cell antigens (BDCAs) [13,14]. In this study, we address several novel aspects of human DC development in NOD/SCID mice transplanted with human CD34 + cells and demonstrate that there is a direct correlation between each of the DC progenitor and precursor populations normally found in humans and those found in transplanted mice.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant HLA-DR mod CD11c Ϫ DC subset (comprising 61.4% Ϯ 11.6 SD of the total DC population) was CD123 ϩ , CD4 ϩ , CD68 hi , and closely resembled in phenotype, morphology, and localization near paracortical high endothelial venules 28 the plasmacytoid tonsil DCs 17 and immature CD11c Ϫ DCs described in blood, 9,10 bone marrow, and thymus. 10 As a result, it has been suggested that this tonsil DC subset may be derived from CD11c Ϫ immature/lymphoid blood DCs. 12,17 Our study further extends the phenotype of plasmacytoid DCs and demonstrates that they express p55, CD45RB, CD24 (vib-e3), low levels of HLA-DP, but lack DC activation markers and 4-1BB ligand.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]14 Three tonsil DC subsets consisting of GCDCs, 18 plasmacytoid DCs, 17 and IDCs 16 have been described previously. Our new methodology has the advantage of avoiding potential problems of antigenic changes associated with in vitro culture 19 plus the biases induced by positive selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation